Análisis del impacto comercial de muebles & muebles electrodomésticos de la ciudad de Tunja, causado por la llegada de almacenes de cadena (2022)
his project develops the stages of diagnosis, analysis and proposals to mitigate the impact on the commercialization of furniture and appliances from the Muebles & Muebles Electrodomésticos store in the city of Tunja. Within the diagnostic stage, aspects such as the current situation of the trade of private companies and chain stores were taken into account. For the analysis stage, the satisfactions of private companies with respect to the commercialization of their products was taken into account and in the final stage proposals are given that help private companies to strengthen themselves against the market of large chain stores that every day is more competitive.